Experience in the Surgical Management of Two Cases with Acromegaly - Eka J Wahjoepramono (Jurnal llmu Bedah Indonesia, 2007)
Acromegaly is a chronic disorder that usually develops over many years due to long term exposure to elevated levels of growth hormone (GH) most typically caused by a somatotrophic cell pituitary adenoma. It has an annual incidence of approximately 3-4 cases / million. A diagnosis of acromegaly is made based on the clinical presentation, biochemical and radiologic finding. The classical feature is the change in appearance and acral enlargement. No single therapy is comprehensively successful in controlling the disease. Surgical, medical and radiation treatments are available for lowering GH and insulin-like growth factor I (IGF-I) hypersecretion, controlling pituitary tumor mass effects, and lowering morbidity.